2015
DOI: 10.1021/ja510067v
|View full text |Cite
|
Sign up to set email alerts
|

Covalency in Lanthanides. An X-ray Absorption Spectroscopy and Density Functional Theory Study of LnCl6x(x= 3, 2)

Abstract: Covalency in Ln-Cl bonds of Oh-LnCl6(x-) (x = 3 for Ln = Ce(III), Nd(III), Sm(III), Eu(III), Gd(III); x = 2 for Ln = Ce(IV)) anions has been investigated, primarily using Cl K-edge X-ray absorption spectroscopy (XAS) and time-dependent density functional theory (TDDFT); however, Ce L3,2-edge and M5,4-edge XAS were also used to characterize CeCl6(x-) (x = 2, 3). The M5,4-edge XAS spectra were modeled using configuration interaction calculations. The results were evaluated as a function of (1) the lanthanide (Ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
282
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(321 citation statements)
references
References 149 publications
33
282
0
Order By: Relevance
“…For comparison, a ground state composition of 75% 3d 10 4f 0 and 25% 3d 10 L4f 1 was found previously to model the LMCT energy (3.3 eV) for (Et4N)2CeCl6 as defined by ΔEgs = 2.5 eV, ΔEfs = -1.5 eV, and Tgs = Tfs = 0.70. 57 Hence, the CTM4XAS calculations suggest that there is slightly more 4f 1 character in the ground state of CeLK4 (38%) than in (Et4N)2CeCl6 (25%). The relatively low percentages of 4f 1 character observed for these two compounds suggested that the LMCT configuration has a smaller contribution to the ground state than previously reported for (C8H8)2Ce, based on L3-edge XANES spectroscopy (89%) and multiconfiguration interaction calculations (80%).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…For comparison, a ground state composition of 75% 3d 10 4f 0 and 25% 3d 10 L4f 1 was found previously to model the LMCT energy (3.3 eV) for (Et4N)2CeCl6 as defined by ΔEgs = 2.5 eV, ΔEfs = -1.5 eV, and Tgs = Tfs = 0.70. 57 Hence, the CTM4XAS calculations suggest that there is slightly more 4f 1 character in the ground state of CeLK4 (38%) than in (Et4N)2CeCl6 (25%). The relatively low percentages of 4f 1 character observed for these two compounds suggested that the LMCT configuration has a smaller contribution to the ground state than previously reported for (C8H8)2Ce, based on L3-edge XANES spectroscopy (89%) and multiconfiguration interaction calculations (80%).…”
Section: Resultsmentioning
confidence: 91%
“…7,12,[17][18][19]22,[24][25][26][154][155][156][157] However, the role of final state effects including core-hole induced changes in 4f occupancy, and other physical phenomena, remains controversial and is the subject of a persistent debate. 18,33,[35][36] Figure 8 compares the background-subtracted and normalized Ce L3-edge XANES spectra of CeLK4 and reference compounds CeO2, 158 [Et4N]2[CeCl6], 57 and (C8H8)2Ce. 99 Each of the L3-edges exhibited a double-peak structure that is characteristic of published data for formally Ce 4+ compounds such as CeO2, Ce(SO4)2, and CeF4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The forces of electrostatic attraction between ions in a compound cause the chemical bonding of ions with the surrounding ions of opposite charge. However, it has been a longstanding mystery concerning 4f electrons of RE elements when evaluating their chemical bonding ability [4][5][6]. Very recently, we discovered that RE elements can form three types of chemical bonding, namely sp hybridization, spd hybridization, and spdf hybridization [7].…”
mentioning
confidence: 99%